Anti-MIT3 antibodies in systemic sclerosis. (22nd February 2011) - Cavazzana, I; Taraborelli, M; Ceribelli, A; Fredi, M; Norman, G; Satoh, M; Franceschini, F
Abstract : Background and objectives: Antimitochondrial (AMA) is considered the serological hallmark of primary biliary cirrhosis (PBC). Other autoantibodies recognising nuclear dots (Sp100) and nuclear pore complex proteins (gp-210) are associated to severe PBC, but they are found by less available methods. An ELISA with a combination of three mitochondrial antigens (MIT3), Sp100 and gp-210 has been recently developed. The aim of our study was to analyse the prevalence, associations and the fine specificity of antibodies to MIT3, Sp100 and gp210 in a cohort of Italian patients affected by systemic sclerosis (SSc). Materials and methods: 201 sera were analysed by ELISA (Quanta Lite TM ELISA; INOVA Diagnostics Inc, San Diego, California, USA) for the detection of antibodies to MIT3 (using goat anti-human IgA and IgG antibodies), Sp100 and gp210. Antinuclear, anti-ENA and anti-RNA polymerase III were detected by indirect immunofluorescence (IIF), counterimmunoelectrophoresis and ELISA, respectively. AMA were identified by IIF on rodent kidney/stomach/liver tissue sections. The diagnosis of SSc and PBC were assessed according to LeRoy criteria and EASL Clinical Practice Guidelines. More than 99% of patients were Caucasians of Italian ancestry. Results: Antibodies to combination of MIT3, gp210 or Sp100 (anti-PBC screen+) were detected in 21% of cases (43 sera): anti-MIT3 were found in 36, anti-Sp100 in 5 and anti-gp210 in 1 serum. Anticentromere (ACA) and AMA were more frequently detected in anti-PBC screen+ when compared with 158 negative group (p=0.0005 and p=0.001). When the authors considered only ACA+ patients, AMA and PBC were more frequently found in anti-PBC screen+ cases (p=0.02 and p=0.0009). Analysing the anti-MIT3 isotypes (36 sera), the authors found isolated IgG in 44.5%, IgA in 33.4%, IgG+IgA in 22%. Autoantibodies and clinical features of SSc didn't show a different distribution between groups, except for skin ulcers and pulmonary hypertension more frequently detected in isolated IgG and in total IgG anti-MIT3 cases, respectively. AMA were more frequently detected in IgA+IgG versus IgA or IgG anti-MIT3 groups (p=0.005 and p=0.002). IgA+IgG anti-MIT3 showed a more frequent diagnosis of PBC and elevation of serum ALP (considered a marker of liver disease severity) despite of urso-deoxycholic acid treatment, when compared with others (p=0.014 and p=0.04). Anti-MIT3 antibodies showed a good sensitivity and specificity (75% and 85%, respectively) for PBC diagnosis. Conclusions: The availability of fully automated ELISA could enhance the possibility of finding different autoantibodies considered markers of PBC in routine laboratory analysis, avoiding assays with diversified antigen sources. The anti-MIT3 isotypes characterisation could improve the assessment of patients with PBC, with higher risk of disease severity.